The detail out of sight: the towers of Rouen’s Cathedral (Palíndromo, 2022)
The detail can assume several dimensions, between particularities, parts in a whole, fragments, minimal, marginal and liminal elements, to the character of an autonomous, symbolic, and a significant element, a modifying device, even a random or insignificant occurrence or, on the contrary, a formal overstatement.The term detail has an extraordinary polysemy, applying to a great kind of situations, therefore details, in the context of the history of art and aesthetics, will not all be the same, in terms of discourse, intention, meaning and character; they will not arise for the same reasons; won’t have the same expressive force, nor should be read according to generalist models of interpretation. The complexion of the detail hinders the objectivity and fluidity of the analysis, and, above all, the construction of clean and finished narratives. Studying the detail can, by all means, constitute by itself a labour that originates fragmentary speeches.After a theoretical introduction regarding the detail, in the density of its dimensions, we will analyse the case of the order of the three towers of Rouen's cathedral (Normandy, France): the Saint-Romain, the Manteiga, and the idealization of the spire over the cruise tower. The towers were criticized by the incumbents due to their excessive detail and the meticulous and time-consuming cutting of the stone for works out of sight. The last work, considered the pinnacle of detail, would never be built.The unresolved issue is related to the just reasons for the harsh criticisms from the cathedral chapter which lead to the resistance undertaken by the artists, who defended the detail even at the risk of their work.
Keywords: Detail; Sculpture; Rouen; Cathedral; Invisibility